Assessing the Impact of Environmental, Social and Governance Indicators on Corporate Financial Performance - Zhu Jiang; Prince Asare Vitenu-Sackey (SAGE Open)
The rise in the interest in ESG-Financial performance nexus has brought with it both opportunities and challenges for companies managing their risk-return dynamics with shareholders and other stakeholders. This paper investigates the impact of environmental, social, and governance indicators on the corporate financial performance of 249 public companies selected from Europe, the Middle East and Africa (EMEA) and the Latin American economic regions from 2010 to 2020. We use the panel generalised quantile instrumental variable and common correlated effect mean group estimators, which are robust to cross-sectional heterogeneity, endogeneity and cross-sectional dependence issues. Our findings suggest that ESG plays a significant role in influencing the financial performance of companies. Moreover, high-performing firms tend to see positive effects from ESG indicators, while low-performing firms may benefit from corporate social responsibility. By incorporating unobserved common factors to account for potential cross-sectional dependence, we found that the financial performance of firms in the lower and middle quantiles could be significantly enhanced through improved ESG disclosure and performance. In addition, the relationship between ESG indicators and leverage tends to favour high-performing firms over lower-performing ones. We confirm that the relationship between ESG indicators and corporate financial performance is heterogeneous, and there are possible unobserved common factors that could potentially bias the estimated coefficients. However, our econometric methods are robust and flexible enough to address these econometric issues.